2014
DOI: 10.1111/mmi.12637
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of heptaprenyl diphosphate sensitizes Bacillus subtilis to bacitracin: implications for the mechanism of resistance mediated by the BceAB transporter

Abstract: Heptaprenyl diphosphate (C35-PP) is an isoprenoid intermediate in the synthesis of both menaquinone and the sesquarterpenoids. We demonstrate that inactivation of ytpB, encoding a C35-PP utilizing enzyme required for sesquarterpenoid synthesis, leads to an increased sensitivity to bacitracin, an antibiotic that binds undecaprenyl pyrophosphate (C55-PP), a key intermediate in cell wall synthesis. Genetic studies indicate that bacitracin sensitivity is due to accumulation of C35-PP, rather than the absence of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 59 publications
3
47
0
Order By: Relevance
“…Taking this hypothesis one step further, it was recently proposed that BceAB of B. subtilis does not transport bacitracin at all, but instead it acts by flipping the target molecule UPP to the cytoplasmic side of the membrane (30). To address this important question, here we used SPR spectroscopy to test whether the permease BceB could bind bacitracin in the absence of the native membrane environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking this hypothesis one step further, it was recently proposed that BceAB of B. subtilis does not transport bacitracin at all, but instead it acts by flipping the target molecule UPP to the cytoplasmic side of the membrane (30). To address this important question, here we used SPR spectroscopy to test whether the permease BceB could bind bacitracin in the absence of the native membrane environment.…”
Section: Discussionmentioning
confidence: 99%
“…Possible scenarios that have been discussed include removal of cellassociated peptides to the culture supernatant or import of the antibiotics for subsequent degradation (17,18,25). More recently, it was proposed that BceAB might in fact not transport bacitracin at all but rather flip UPP to the cytoplasmic face of the membrane to prevent bacitracin binding (30). Addressing this important question is hampered by the lack of knowledge on the transporter's true substrate; it is unclear whether BceAB is able to bind free bacitracin as its substrate or whether it instead recognizes a membrane-associated UPP-bacitracin complex.…”
mentioning
confidence: 99%
“…Disk diffusion assays were performed as previously described (21). Overnight cultures of test strains were reinoculated into fresh LB liquid medium and grown to early log phase (optical density at 600 nm [OD 600 ] of ϳ0.4), and a 100-l aliquot of the culture was mixed briefly with 4 ml LB soft agar (containing 0.75% agar, kept at 50°C) before being poured onto LB plates (containing 15 ml LB with 1.5% agar).…”
Section: Methodsmentioning
confidence: 99%
“…The most widely used antibiotic of this class is bacitracin, which binds tightly to the pyrophosphate group on surface-exposed UPP to inhibit its dephosphorylation (18). Bacitracin also activates the M stress response, which contributes to bacitracin resistance by increasing the synthesis of BcrC (19)(20)(21), a predicted UPP-Pase presumed to act on the outer face of the membrane to convert UPP (the target of bacitracin) into Und-P (22). Finally, a variety of structurally diverse antibiotics, including glycopeptides and lantibiotics, bind to lipid II, which serves to both inhibit cell wall synthesis and sequester the UPP carrier lipid (23).…”
mentioning
confidence: 99%
“…This view was supported by in vitro results indicating that BceB is able to bind bacitracin directly (Dintner et al 2014). In vivo results, on the other hand, argued for BceB binding UPP and even suggested that this transporter might play a role as a UPP flippase of the cycle (Kingston et al 2014). The most recent observation that a tightened bottleneck in the lipid II cycle, provoked by the absence of the UPP phosphatase BcrC, increases P bceA activity (Radeck et al 2016) indeed points towards UPP as a possible binding partner for BceB.…”
Section: Drug Sensing Versus Target Sensingmentioning
confidence: 83%